PENGGUNAAN MEDIA SOSIAL DALAM MEMBERDAYAKAN MASYARAKAT MISKIN DI KOTA BENGKULU (Studi Kasus Pada Lembaga Swadaya Masyarakat “Ketimbang Ngemis Bengkulu”) - Dwi Fitri Utami; Ilham Adbullah; Sofino Sofino (UNIB Press, Universitas Bengkulu, 2019)
The purpose of the research to describe a social media as empowering instrumen a poor society in bengkulu city which is conducted by a Non Govermental Organization (NGO’s) “Ketimbang Ngemis Bengkulu”. The method analysis intervew, observation, and documentation. The step studied analysis form data reduction, data presentation, exposure result and conculsion of data validity using analysis methods triangulation begins and triangulation time, subject and technique. The result prove that empowerment community ‘Ketimbang Ngemis Bengkulu’ conducted us capital distribution assistance. Raising, bazaar fairs, garage sale, given to inspirational people with disabilities and age limitations who choose not to beg or become homeless. The role of social media to empowering is among others, as a medium for mobilizing information to related a inspirational figures, or succour. There are stages community empowerment are starting from preparation, implementation and evaluation. The empowerment program by ‘ketimbang ngemis bengkulu’ is very useful to improve the habbits and create awareness towards fellow being human. Keywords : Media social, Empowering, poor society